The Process of Restoration of Objects of Design as a Critical State Morphology and Colour in Images of Visual Cognitive Information Dynamic Systems (VKIDS) - V.L, Zhukov; L.T, Zhukova (International Journal of Engineering and Technology, 2018)
In this article, the restoration is investigated from the perspective of self-organizing system, as some oscillation process in the state of "life" of design objects: from chaos to its creation and back to chaos as a result of losses and again to its original author's version as a result of restoration work.Â Â Â